TANTANGAN DAN PELUANG DALAM PENGELOLAAN WAKAF SEBAGAI SUMBER PENDANAAN PENDIDIKAN DI ERA MODERN - Aprilliantoni, Aprilliantoni; Fahrun, Elva; Ramadhan, Fajar (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Waqf, as one of the philanthropic instruments in Islam, has great potential to become a sustainable source of educational funding in the modern era. Waqf is not limited to land or buildings; it has also evolved into various forms such as cash waqf and waqf sukuk, which can be used to finance educational institutions. History shows the significant contribution of waqf to the development of education, especially during the Islamic Dynasty. However, challenges in educational funding are increasing as education costs continue to soar. In this context, waqf can serve as an effective alternative solution. Professional and transparent management of waqf is crucial to ensure that the collected funds can be utilized optimally. Additionally, the use of technology in waqf management is a key factor in enhancing efficiency and transparency. This research aims to explore the challenges and opportunities in managing waqf as a source of educational funding in Indonesia.